THE ROLE OF CORPORATE GOVERNANCE AND FINANCIAL INDICATORS IN PREDICTING THE FINANCIAL DISTRESS - Irene Christi Wati; Frisky Jeremy Kasingku (SEAN Institute, 2022)
The purpose of this study is to analyze the role of good corporate governance and financial indicators in predicting the financial distress in real estate and property sector companies for the 2018-2020 period. This study used secondary data by obtaining data from the official website of the Indonesia Stock Exchange and related companies. Quantitative approach is used for this research. Furthermore, sample determination is carried out based on the purposive sampling method. The data analysis method used is logistic regression analysis. The results of this study found that, partially, the board of directors can predict the occurrence of financial distress, while independent commissioners, leverage and liquidity cannot predict the occurrence of financial distress in real estate and property companies. Furthermore, simultaneously, corporate governance and financial indicators can predict the financial distress